A Chemically Triggered and Thermally Switched Dielectric Constant Transition in a Metal Cyanide Based Crystal - Shi, Chao; Zhang, Xi; Cai, Ying; Yao, Ye-Feng; Zhang, Wen (Angewandte Chemie International Edition, 2015)
A dielectric constant transition is chemically triggered and thermally switched in (HPy)2[Na(H2O)Co(CN)6] (2, HPy=pyridinium cation) by single‐crystal‐to‐single‐crystal transformation and structural phase transition, respectively. Upon dehydration, (HPy)2[Na(H2O)2Co(CN)6] (1) transforms to its semi‐hydrated form 2, accompanying a transition from a low‐dielectric state to a high‐dielectric state, and vice versa. This dielectric switch is also realized by a structural phase transition in 2 that occurs between room‐ and low‐temperature phases, and which corresponds to high‐ and low‐dielectric states, respectively. The switching property is due to the variation in the environment surrounding the HPy cation, that is, the hydrogen‐bonding interactions and the crystal packing, which exert predominant influences on the dynamics of the cations that transit between the static and motional states. A dielectric constant transition is observed in (HPy)2[Na(H2O)Co(CN)6] (HPy=pyridinium cation). This transition is chemically triggered by water in a single‐crystal‐to‐single‐crystal transformation (see picture; right) and thermally switched (left) in a structural phase transition.